An experience of being split - a discourse analytical approach to how psychomotor physiotherapy position itself as a dicipline and treatment approach - Silje Kristine Rake; Birgitte Ahlsen (Fysioterapeuten, 2022)
Aim: To investigate how psychomotor physiotherapy present its treatment approach and position itself in the treatment field.